The Role of E-Wallet's Actual Consumer in Indonesia with Policy Perspective and Consumer Perception Using Latent Dirichlet Allocation (LDA) Method - Reni; Elsye Vanomy, Afrianti (FIA UB, 2023)
The purpose of the research to analyze how the role of policy provisions issued by Central Bank of Indonesia, known as BI and The Financial Services Authority related to non-cash payment systems, especially E-wallets, it has an important role to E-wallet’s actual consumer in Indonesia. The next point is how does consumer perceptions has the important role in its interest for using E-wallets in Indonesia. The research’s type is such qualitative research, by using Topic Modeling by web scrapping from online news article. The amount of the articles is 1,215. This research using Phyton Software version 3.10 for help for analyzing. The results of the current research using LDA method include topic 1 is 45.9%, topic 2 is 32.9% and topic 3 is 21.2%. The conclusion of the research show that the policies regarding E-wallets, issued from BI and the Financial Services Authority, it has an important role towards to the actual consumer from E-wallets in Indonesia. From the point of view of consumer perceptions regarding E-wallets, it has an important role in the interest of consumer's actual in using E-wallets.